A Teacher’s Terminal Illness in the Secondary Classroom: The Effects of Disclosure - Sarah Hochstetler (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
How does it affect learning when cancer becomes the prevailing metaphor through which students see their teacher?